Stress and coping strategies: basis for resiliency program for adolescents - Jericha G. Macalinao 4 0 16; 5 (2017)
ABSTRACT: The study aims to measure the relationship between perceived stress and coping strategies among psychology students from Pamantasan ng Lungsod ng Maynila. A correlation study was conducted among 150 Psychology students from Pamantasan ng Lungsod ng Maynila with the used of Pearson R Correlation. Purposive sampling technique was also used to select participants. The perceived stress scale was used to assess the level of perceive stress while brief cope was used to assess coping strategies. The study found that most of the students have moderate level of perceived stress and that the top 5 commonly used coping strategies are acceptance, planning positive reframing, ac tive coping and self-distraction. The study also found that there is a significant negative relationship between perceived stress and planning, positive reframing and active coping which indicates the null hypothesis to be rejected. As the level of perceived stress decreases, the more frequent one uses planning, acceptance and active coping as their coping strategies and as the level of perceived stress increases, less frequent one uses planning, acceptance and active coping as their coping strategies. It is important for adolescents and students to know their stress level and learn ways on how to deal with it with the use of programs.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2